Development of a Geography Module with a Disaster Mitigation Learning Model Based on the Concept of Local Wisdom in Disaster Preparedness - Irwan Abdullah; Enok Maryani (Universitas Negeri Medan, 2024)
Ternate City is one of the areas that has a high level of disaster vulnerability in Indonesia. In addition, the level of public awareness and knowledge about disaster experiences the highest level of vulnerability to local disasters, such as landslides, earthquakes, volcanic eruptions. as for the purpose of this research is). Developing a disaster mitigation learning model based on the concept of local wisdom in disaster preparedness?. And designing disaster mitigation lessons based on the concept of local wisdom in disaster preparedness? . The 4-d model consists of four stages, namely: definition, design, development, and deployment. Researchers have developed a disaster mitigation geography learning module based on the concept of local wisdom in disaster preparedness, especially at State Senior High School 5 Ternate City. The results of the development of learning modules can be seen from the aspect of content 82.23% with proper qualifications, the aspect of the science and technology community model 85% with very decent qualifications, the aspect of format 82% with very decent qualifications, the language aspect 93% with very good qualifications. proper qualifications and presentation aspects of 80% with proper qualifications. While the average value of the validator results is 85.5%. in addition to disaster mitigation learning materials, namely, types of disaster characteristics and disaster management cycles, distribution of disaster-prone areas in Indonesia, disaster management through education, local wisdom and use of technology and the role of society in natural disaster mitigation. In addition, the subjects at State Senior High School 5 Kota Ternate showed that the assessment results of highly qualified students were 75%, and the assessment of students with very high qualifications was 8.33%, while those with high qualifications were moderate student assessment qualifications of 16%. It can be concluded that teacher learning teaches students to understand learning material well, both from learning modules and community technology science models that are applied in learningKeywords: Geography Module, Disaster Mitigation, Local wisdom, Disaster Preparedness